Implementasi Strategi Problem Posing Dalam Pembelajaran Matematika Terhadap Kemampuan Kognitif Ditinjau Dari Motivasi Belajar Siswa Kelas VII Semester Genap MTs Muhammadiyah Blimbing Tahun Ajaran 2014/2015 - Noorsabekti, Arif; , Prof. Dr. Budi Murtiyasa, M.Kom (2015)
This study aims to know: (1) Effect of Problem Posing strategy towards the achievement of students' cognitive abilities in mathematics learning, (2) The effect of the level of motivation toward achieving the student's cognitive ability in mathematics learning, (3) Effects of Problem Posing interaction between strategy and level of motivation learning to the achievement of the cognitive abilities of students in learning mathematics. The study was an experimental study. The population of this study were all students of class VII MTs Muhammadiyah Blimbing academic year 2014/ 2015. The sample was a class VII E as an experimental class with 27 students and class VII C as a control class with 29 students. The sampling technique was cluster random sampling. The method of data collection is a test and questionnaire as well as the principal method of documentation as auxiliary method. Research analysis techniques using two-way analysis of variance is not the same cells that were previously done using methods Lilliefors test for normality and homogeneity test using the Bartlett method. Results of research on the α = 5% was obtained: (1) There is the effect of applying the strategy to the achievement of Problem Posing cognitive abilities in mathematics with FA = 4,076> Ftable = 4.048; (2) There is the influence of the level of motivation toward achievement of cognitive abilities in mathematics with FB = 24.676> Ftable = 3,198; (3) There is no interaction effect between strategy Problem Posing and level of motivation toward achievement of the cognitive abilities of students in learning mathematics with FAB = 1,495 <Ftable = 3.198.